Validation of an instrument to assess food diversity in women of childbearing age in Medellín, Colombia (2022)
ABSTRACT: Objective: To validate a Food Diversity Questionnaire (CDA, for its name in Spanish) that identifies the prevalence of the risk of deficiency in the intake of eleven micronutrients. Design: The CDA paper form, an online application for data entry and handling, was designed and compared with the 24-h recall (24HR) as a reference method. All data were processed in Personal Computer Software for Intake Distribution Estimation (PC-SIDE) v1 software. A descriptive analysis and comparisons between prevalence, concordance and reproducibility analyses were performed. Setting: Medellín, Colombia. Participants: Women of childbearing age between 19 and 50 years (n 186) who worked for the Buen Comienzo programme in 2019. Results: When comparing the adjusted 24HR technique and the CDA, there was no significant difference in population-level data at risk of deficiency in any micronutrient intake. However, based on individual-level data of the best linear unbiased predictor, the concordance analyses were weak, and although agreements were high according to the diagnostic performance tests, a good ability to detect deficiency was only observed in a few nutrients: vitamin A 100·0 %, Ca 98·7 %, Fe 92·8 %, folates 91·6 %, and pyridoxine 81·8 %. Conclusions: The CDA validated in this study is useful and faster at evaluating population-level data at risk of deficiency in the intake of Ca, Fe, Zn, thiamine, riboflavin, niacin, pyridoxine, folates, vitamin B12, vitamin C and vitamin A. Based on individual-level data, a good ability to detect deficiencies was observed in the intake of vitamin A, Ca, Fe, folates and pyridoxine.